Influence of Masonry Infill on Seismic Design Factors of Reinforced-Concrete Buildings - Shendkar, Mangeshkumar R.; Kontoni, Denise-Penelope N.; Işik, Ercan; Mandal, Sasankasekhar; Maiti, Pabitra Ranjan; Harirchian, Ehsan (My University, 2022)
Infill walls are the most common separator panels in typical reinforced-concrete (RC) frame structures. It is crucial to investigate the influence of the infill walls on the earthquake behavior of RC frames. The load resistance of infill materials was often not taken into account in the designing phase, whereas the infill walls have significant contributions to the structural behavior under lateral and vertical loadings. A three-dimensional 4-story RC building is designed, and in order to make a realistic model, different infill walls configurations were taken into account with the openings in the infill. Four different models were created for structural analysis for infill wall effects, namely, full RC infilled frame (Model I), corner infill at ground story RC infilled frame (Model II), open ground story RC infilled frame (Model III), and bare RC frame (Model IV). Static adaptive pushover analysis has been performed for all structural models by using the SeismoStruct software. The double strut nonlinear cyclic model was used for modeling the infill walls. In this study, three different compressive strengths of infill walls are taken into consideration, and the effects on seismic design factors (namely, the response reduction factor, the ductility, the overstrength factor, and the deflection factor) are calculated. The obtained values of the response reduction factor (R) are compared with the given values in the BIS code. The results show that the R factors of all RC infilled frames are decreased when the compressive strength of the masonry infill reduces. However, the R values of bare frames are less than the corresponding values recommended in the BIS code. It is worth noting that the National Earthquake Hazards Reduction Program (NEHRP) provisions underestimate the deflection factors of the reinforced-concrete (RC) frames according to the evaluated deflection factors of the herein studied RC frames.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Compressive strength; Concrete buildings; Earthquakes; Infill drilling; Seismic design; Structural analysis; Structural frames; Walls (structural partitions); Frame models; Infill walls; Infilled frame; Masonry infills; Reduction factor; Reinforced concrete buildings; Reinforced concrete frame structures; Reinforced concrete frames; Response reductions; Seismic design factors; Reinforced concrete